Numerical investigations of single mode gyrotron equation - Cepitis, Janis; Kalis, Harijs; Reinfelds, Andrejs (Mathematical Modelling and Analysis, 2009)
A stationary problem with the integral boundary condition arising in the mathematical modelling of a gyrotron is numerically investigated. The Chebyshev's polynomials of the second kind are used as the tool of calculations. The main result with physical meaning is the possibility to determine the maximal value of electrons efficiency.First published online: 14 Oct 2010